The Role of Temporal Contingency and Integrity of Visual Inputs in the Sense of Agency: A Psychophysical Study - Mizuhara, Hiroaki; Uhlhaas, Peter (Frontiers in Psychology, 2021)
The sense of agency is a subjective feeling that one’s own actions drive action outcomes. A potential mechanism underlying the sense of agency is the comparison between action and incoming sensory inputs. Previous studies have focused primarily on the temporal contingency between actions and sensory inputs; however, the integrity of visual inputs has not been fully addressed. In the current study, we developed a psychophysical task to examine the contribution of visual inputs as well as temporal contingency toward the sense of agency. Specifically, participants were required to track a target on a sinusoidal curve on a computer screen. The visual integrity of sensory inputs was manipulated by gradually occluding the computer cursor, and participants were asked to report the sense of agency on a nine-point Likert scale. Temporal contingency was manipulated by varying the delay between finger movements on a touchpad and cursor movements. The results showed that the sense of agency was influenced by both visual integrity and temporal contingency. These results were then discussed in the context of current models that have proposed that the sense of agency emerges from the comparison of visual inputs with motor commands.